INTEGRASI PRINSIP GREEN PORT DALAM REGULASI KEPEMILIKAN LAHAN DAN PENEGAKAN HUKUM LINGKUNGAN DI PELABUHAN INDONESIA: Integration of Green Port Principles in Land Ownership Regulations and Environmental Law Enforcement in Indonesian Ports - Antara, I Wayan; Budiarta, I Dewa Gede; Jekalaya, I Wayan; Suartini, Made (Ganec Swara, 2025)
Ports as engines of growth face a dilemma between driving economic growth and preserving the environment. This study aims to analyze the integration of Green Port principles within the regulations governing land ownership and environmental law enforcement in Indonesian ports. The research employs a normative juridical method with statutory and conceptual approaches. The results indicate that land ownership regulations for foreigners create governance complexity and gaps, while environmental law enforcement through the strict liability and polluter pays principles remains ineffective due to difficulties in identifying polluters, force majeure claims, and overlapping authorities. As a solution, this study proposes an integrated Green Port Policy framework built on three pillars: the integration of land permits with environmental obligations, integrated law enforcement through inter-institutional synergy, and a system of incentives and disincentives. This framework is expected to create sustainable and equitable port governance